Research of composite fuels thermophysical properties based on low-grade coals with addition of fine sawdust and flour industry wastes; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Yankovsky S. A. Stanislav Aleksandrovich; Tolokolnikov A. A. Anton Andreevich; Matveev A. S. Aleksandr Sergeevich; Marysheva Ya. V. Yana Vladimirovna (2017, 2017)
Title screen